Strategic Information Systems Planning in the Sheet Glass Distribution Industry (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
This study aims to design strategic planning for Information Systems (IS) and Information Technology (IT) at PT. Sentral Kaca Cirebon, a flat glass distributor facing operational efficiency challenges. Amidst the increasingly fierce competition in the building materials industry, the current manual processes are the main obstacle to company agility. This study uses a qualitative method with the Ward and Peppard framework of the Digital Strategy Model (DSM) methodology to align business strategy with IS/IT strategy. Environmental analysis was conducted using SWOT analysis, Porter's value chain, Porter's five forces, PESTLE, and McFarlan's strategic grid. The results of the study formulate a roadmap and portfolio of future applications called "SISKA" (Central Glass Information System), which includes an inventory management module, a B2B customer portal, and a glass cutting optimization system. The implementation of this strategy is projected to improve operational efficiency, stock data accuracy, and the company's competitiveness in the West Java regional market.